Biofilm formation on zirconia and titanium over time—An in vivo model study. Issue 9 (9th July 2020) - Desch, Anton; Freifrau von Maltzahn, Nadine; Stumpp, Nico; Dalton, Marly; Yang, Ines; Stiesch, Meike
Abstract: Objectives: The aim of this study was to evaluate volume, vitality and diversity of biofilms on the abutment materials zirconia and titanium as a function of time using an in vivo model for the biofilm formation. Materials and methods: The development of biofilms on zirconia and titanium grade 4 test specimens in the human oral cavity over time was analysed. After pretreatment, a total of 96 titanium and 96 zirconia discs were fixed on 12 composite splints, which were worn by 12 volunteers. After 6 hr, 24 hr, 3 days and 5 days, biofilms on 48 specimens of each material were analysed with confocal laser scanning microscopy (CLSM). The microbiota composition on the other 48 test specimens was examined using full‐length 16S sequence analysis. Statistical analysis was performed by SPSS and R, and level of significance was set at 0.05. Results: Confocal laser scanning microscopy analysis of the biofilms revealed significant changes in volume over time on zirconia and titanium. The material did not significantly influence the volume or live/dead ratio at the individual time points. The composition of the microbiome was influenced by the age of the biofilm, but not by the material of the test specimen. The most frequently found bacteria were Streptococcus spp., followed by Neisseria spp., Rothia spp., Haemophilus spp., Gemella spp. and Abiotrophia spp. Conclusions: On both materials, the quantity and diversity of the microbiome increased over time. Apart from a slight difference in Veillonella abundance at one time point, there were no significant differences between zirconia and titanium.